Lexical categories : verbs, nouns, and adjectives - Baker, Mark C. (Cambridge studies in linguistics, 2003)
Mark C. Baker investigates the fundamental nature of nouns, verbs, and adjectives. He claims that the various superficial differences that are found in particular languages have a single underlying source which can be used to give better definitions of these 'parts of speech'.